2009
DOI: 10.1111/j.1365-2656.2009.01595.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat‐specific differences in adult survival rates and its links to parental workload and on‐nest predation

Abstract: Summary1. Adult survival rates strongly affect population growth, but few studies have quantified if and why adult survival differs between breeding habitats. We investigated potential causes of habitatspecific adult survival rates for male and female northern wheatears (Oenanthe oenanthe L.) breeding in Swedish farmland. 2. We used multistate mark-recapture models based on 1263 breeding records between 1993 and 2007 to estimate survival rates based on habitat-type (SHORT vs. TALL ground vegetation) and breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
117
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(123 citation statements)
references
References 74 publications
5
117
1
Order By: Relevance
“…This pattern is different from that found in the majority of other bird species, where annual survival is typically higher for males than for females (e.g. Stokke et al 2005;Low et al 2010). Interestingly, however, Thaxter et al (2006) found opposite patterns (higher and lower male survival compared to the females) in two populations of British Reed Warblers, suggesting that sexbased survival and/or emigration may be site-specific in the species.…”
Section: Discussioncontrasting
confidence: 75%
“…This pattern is different from that found in the majority of other bird species, where annual survival is typically higher for males than for females (e.g. Stokke et al 2005;Low et al 2010). Interestingly, however, Thaxter et al (2006) found opposite patterns (higher and lower male survival compared to the females) in two populations of British Reed Warblers, suggesting that sexbased survival and/or emigration may be site-specific in the species.…”
Section: Discussioncontrasting
confidence: 75%
“…During egg-laying, female birds gain mass that is not compensated for by increased muscle development, and this may impair escape flight and put gravid females at greater risk (Lee et al 1996). Incubation and brood care are thought to place parent birds at greater predation risk (Vehrencamp 1978, Hartke et al 2006, Low et al 2010), but mortality of parents is much harder to document than mortality of sedentary eggs or prefledged young, and so these risks have not been well documented. Determining event-specific mortality among breeding adults generally requires techniques such as telemetry or video surveillance (Hartke et al 2006, Reidy et al 2009), which often precludes large samples and raises concerns that the methodologies themselves may affect mortality risks (Richardson et al 2009, Barron et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Low et al (2010) found that adult workload is higher in poorer quality habitat for Northern Wheatear Oenanthe oenanthe: the rate of provisioning visits to the nest was the same, but the distances flown per visit were much higher. This variation in adult energy expenditure of up to 30% resulted in a decline in adult survival with decreasing habitat quality.…”
Section: Discussionmentioning
confidence: 99%
“…Within a breeding season, the costs of reproduction can vary (spatially or temporally) between pairs due to heterogeneous environmental variables, such as habitat and/or food availability. Pairs can pass on high costs of reproduction to the number of chicks fledged (Martinez 2012), to juvenile survival (Piper et al 2012), to adult survival (Low et al 2010) or to a combination of these traits (Lambrechts et al 2004, Kerbiriou & Julliard 2007, Santangeli et al 2012, Seward et al 2013. Variation in habitat can therefore potentially influence any demographic parameter.…”
mentioning
confidence: 99%